2013
DOI: 10.1016/j.ypmed.2012.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a measure of knowledge about human papillomavirus (HPV) using item response theory and classical test theory

Abstract: A structurally coherent set of items covering a range of important HPV knowledge was developed. Responses indicated a reliable questionnaire, which allowed the fitting of an IRT model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
141
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(165 citation statements)
references
References 15 publications
1
141
0
2
Order By: Relevance
“…Men and women meeting the study criteria were randomly selected and sent recruitment emails containing a link directing them to the home page of our online survey which was entitled ‘What do you know about HPV?’ The survey was adapted for use in the USA, UK and Australia, changing terminology where appropriate. Further details of the sampling are available elsewhere 20 21. Ethical approval was granted from research ethics committees at Indiana University, USA, University College London, UK and the University of Sydney, Australia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Men and women meeting the study criteria were randomly selected and sent recruitment emails containing a link directing them to the home page of our online survey which was entitled ‘What do you know about HPV?’ The survey was adapted for use in the USA, UK and Australia, changing terminology where appropriate. Further details of the sampling are available elsewhere 20 21. Ethical approval was granted from research ethics committees at Indiana University, USA, University College London, UK and the University of Sydney, Australia.…”
Section: Methodsmentioning
confidence: 99%
“…The scale items can be seen in table 3. The development and validation of the scale is described elsewhere 21. Response options were true/false/don't know, with ‘don't know’ scored as incorrect.…”
Section: Methodsmentioning
confidence: 99%
“…Pre-existing validated HPV knowledge questions were incorporated into the survey where appropriate 17 . This survey tool has been previously used to assess the level of HPV knowledge in the lay population and therefore it was felt that this is the minimal level of knowledge that healthcare professionals should have.…”
Section: Survey Developmentmentioning
confidence: 99%
“…One scale that could be used is that developed by Waller et al [66], which has demonstrated satisfactory psychometric properties and could be appropriately adapted for use to various other populations, for example, adolescents. Prospective longitudinal studies designed and informed by the PAPM as described above, would be more informative providing data on factors that influenced the move from vaccine intention to uptake.…”
Section: Future Research Recommendationsmentioning
confidence: 99%